Experimental study on stepping performance of the control rod hydraulic drive system. (15th December 2022) - Qin, Benke; Yang, Linqing; Bo, Hanliang
Highlights: CRHDS is a new type of built-in control drive technology. The performance experiments of CRHDS are conducted to analyze the influence of characteristic parameters. The process mechanisms are studied to lay the base for the equipment fault diagnosis and engineering application. The direction and guidance are given for the design optimization of CRHDS. Abstract: Control rod hydraulic drive system (CRHDS) is a new type of built-in control rod drive technology. The circuit flow resistance and driving pressure have significant effects on the stepping performance. The related experiments were conducted. Moreover, the mechanisms of step-up and step-down processes were analyzed and the performance characteristic parameters were obtained. Based on the experimental results, the variations of key parameters were analyzed. The analysis results show that the step-up and step-down processes can be divided into three stages, and displacement, cylinder pressure and flowrate correspond to each other. With the increase of circuit flow resistance, the key time parameters of step-up and step-down processes change first rapidly then slowly. With the increase of driving pressure, the step-up time decreases gradually, the step-down time changes little, and the time of pressure change increases slightly. The research results lay the base for the design and optimization for the CRHDS.